Design of distributed fault tolerant control systems - Costa, José Sá da (2019)
When dealing with large-scale complex networked control systems, designing FDI/FTC systems is a very difficult task due to the large number of sensors and actuators spatially distributed and networked connected. Despite the research effort on developing FTC systems for NCS most of these developments still being designed globally leading to centralized FTC solutions inadequate to NCS or, assume the communication network and the process itself as two different entities loosing the potentiality of the integrated design. The FDI/FTC design method presented in this paper is able to use simple and verifiable principles coming mainly from a decentralized design, based on causal modelling partitioning of the NCS and distributed computing using multi-agents systems, allowing the use of well established FDI/FTC methodologies, or new ones, developed taking into account the NCS specificities. The design methodology is made easy using a FTCNS-MAS toolbox introduced in this paper.